Pengaruh Variabel Keuangan dan Non Keuangan terhadap Underpricing Saham Perusahaan yang Melakukan IPO di BEI Tahun 2020-2022 - Dwi Kartika Sari; Diyah Santi Hariyani; Anggita Langgeng Wijaya (FISCAL: Jurnal Akuntansi dan Perpajakan, 2024)
This research is entitled "The Influence of Financial and Non-Financial Variables on the Underpricing of Shares of Companies Conducting Initial Public Offerings (IPO) on the Indonesia Stock Exchange (IDX) in 2020-2022". The purpose of this study is to prove whether there is influence of financial and non-financial variables on underpricing. This research was conducted on companies that conducted an Initial Public Offering (IPO) on the Indonesia Stock Exchange (IDX) and were registered on the development board using a purposive sampling research method, in order to obtain a sample of 75 companies. This study uses a quantitative approach with SmartPLS software. The results of this study indicate that financial variables with indicators of Earning per Share (EPS), Return on Equity (ROE), Return on Assets (ROA) and company size have a significant effect on underpricing, as well as non-financial variables with indicators of the percentage of share ownership have a significant effect against underpricing.Â